Role of mometasone furoate nasal spray versus saline nasal spray in treatment of adenoid hypertrophy: a prospective, randomized study - Monga, Rabia; Bhagat, Sanjeev; Sharma, Vishal; Sahni, Dimple; Singh, Harjinder; Sharma, Dinesh Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Adenoid hypertrophy is a common disorder in the paediatric population, presenting with multiple signs and symptoms ranging from nasal obstruction to obstructive sleep apnoea. Most common symptom is usually nasal airway obstruction. This prospective, randomized study aims to evaluate the efficacy of mometasone furoate spray in reducing size and clinical symptoms in patients with adenoid hypertrophy compared to saline spray. Methods: 60 patients in the age group of 3-11 years were enrolled in the study. Five symptoms were included that were hypo nasal speech, snoring, night cough, open mouth breathing and nasal obstruction which were scored as never=0, mild (sometimes)=1, moderate (less than 50% of times)=2, and severe (constant)=3. Diagnosis of adenoid hypertrophy was made on basis of nasal endoscopy. Results: Significant improvement was seen in individual as well as overall symptom score in group A as compared to group B after 8 weeks of treatment (p<0.001). There was significant improvement in mean adenoid grade as per nasal endoscopy at 8 weeks post therapy (p<0.001) which was not seen after 4 weeks of therapy. Conclusion: Intranasal steroid sprays have good role in decreasing the symptoms of adenoid hypertrophy and has reduced number of adenoidectomies required. The long-term effects as well as optimal duration of therapy is still controversial and needs to be studied further.